Physical Properties of Film Alloys Based on Ferromagnetic and Noble Metals (Review). І. Film Materials Based on Fe and Ag or Au - L.V. Odnodvorets; I.Yu. Protsenko; Yu.M. Shabelnyk; M.O. Shumakova; O.P. Tkach (Журнал нано- та електронної фізики)
The results of analysis of literature and own data on the phase composition, electrophysical and magnetoresistive properties of granular film alloys based on Fe and Ag or Au are present. Analyzed the question about system designations of film structures, which adopted in the literature and does not meet their physical nature in its original state and after annealing. A new system of signs ordered and disordered solid solutions without and with the presence elements of granular state; quasigranular alloys, in which the role played granules of ferromagnetic island films; intermetallic and others was proposed. It is established that the electrophysical properties (temperature coefficient of resistance – TCR and strain coefficient – SC) defined conductive matrix as s.s., and in nanoscale granules realized the ballistic conductivity mechanism that does not affect the value of TCR and SC. In granular film alloys s.s. Au (Fe) + granules at the plastic deformation observed abnormal increase in comparison with the elastic deformation value SC (10 times) at a concentration cFe  55-75 аt. %.